Numerical study of the lateral interactions of two plasma plumes. (7th August 2017) - Yadav, Sharad K; Patel, Bhavesh G; Singh, R K; Das, Amita; Kaw, Predhiman K; Kumar, Ajai
Abstract: A theoretical investigation of interaction between two laterally colliding laser-blow-off plasma plumes in the presence of ambient gas has been carried out. In an earlier work (Patel et al 2012 Phys. Plasmas 19 073105) it has been shown that the dynamics of the expanding laser-blow-off plume against the ambient background gas can be effectively modeled with the help of a simplified hydrodynamic evolution. The same model is adopted here to understand the interaction of the two plumes. It is observed that the qualitative behaviour of the plume dynamics compares reasonably well with the recent experimental work (Kumar et al 2015 Phys. Plasmas 22 063505).